#TITLE_ALTERNATIVE# - NATHANIA YONATHAN (NIM 10104081), VANESSA
Identifying through DNA gives accurate and absolute identity. But on the other hand, this identification requires high cost. If efficiency can be applied, it will be very useful in identifying. Individual identifying through nucleus DNA is using locus of Short Tandem Repeat (STR). Nowadays, by using 13 locus of STR, human identity can be determined. By reducing number of locus STR using correspondence method, we can do an efficiency of time and cost. Contingency locus and allele is made from STR database, and then will be determined an optimal projection plane through Singular Value Decomposition (SVD). Projection of locus and allele on the projection plane gives information of locus clustering based on similarity of allele. This clustering gives solution of reducing problem. In case study of 9 locus of STR and 103 alleles, correspondence method recommends 5 groups of locus, those are {1,2}, {3}, {4,6}, {5}, and {7,8,9}. One locus from each group will be manually selected which minimize duplication. This selection give result choosing 5 locus STR,{1,3,5,6,8} give 100% in quality, and choose 4 locus of STR, {1,3,5,6} give 99,915% in quality in identification.